PENGEMBANGAN SISTEM DONASI BARANG BEKAS ONLINE BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Novriyanda, Reyhan; Novaliendry, Dony; Farell, Geovanne; Darni, Resmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of information technology has encouraged the digital transformation of various social activities, including the management of used goods donations. However, the donation process is still commonly carried out manually, resulting in difficulties in inventory management, recipient verification, donation distribution, and information transparency. This study aims to develop a web-based used goods donation information system using the Laravel Framework. The system was developed using the Prototype method, which consists of the stages of listening to customer needs, building or revising prototypes, and customer evaluation. The system was implemented using PHP, Laravel Framework, MySQL, Bootstrap, and Visual Studio Code. The developed application involves three main actors, namely administrators, donors, and recipients. The system provides features including donation management, goods categorization, recipient verification, inventory management, donation request management, donor reward points, and profile management. Functional testing indicates that all system features operate according to user requirements. The proposed system is expected to improve the efficiency, transparency, and effectiveness of managing used goods donations while facilitating communication between donors, recipients, and administrators.